Analisis Kebijakan Stunting Melalui Pendekatan Filsafat dan Pengambilan Keputusan Dalam Penanganan Masalah Kesehatan Anak - Amalia Ihsani Mulia Lanasa; Marifa Alysia Nurfakhira; Ribka Davianti Putri (Madani: Jurnal Ilmiah Multidisiplin, 2023)
World Health Organization has a standard stunting prevalence rate of less than 20%. In response to the stunting phenomenon, the Ministry of Health is seeking solutions with various interventions. The issue of stunting is a very important issue. The purpose of this study is to determine the relationship between the philosophical approach and stunting policy, the relationship between the philosophical approach in decision making through handling stunting policies, and the evaluation of decision making by the government through stunting policies in handling child health problems. The method used is qualitative research with literature studies. The research obtained that stunting is reviewed from the ontological side of the reason for its occurrence, epistemology reviews stunting as a new science, axiology reviews stunting from the scientific impact. In addition, it was also found that the relationship between the philosophical approach in government decision making through handling stunting policies, evaluation of target achievement is carried out in 2030, marking the government's commitment to ensuring the sustainability of stunting prevention efforts in a holistic and integrative manner. Finally, the evaluation of government decision-making through stunting policies related to handling child health problems. The problem of stunting, in overcoming child health problems, is closely related to decision-making assessments due to data analysis, collaboration between stakeholders, infrastructure, health interventions, priority programs, and poverty alleviation efforts.